- POTENSI WISATA KULINER DI WARUNG BETAWI HAJI APEN, RAGUNAN, JAKARTA SELATAN: - - Rezka Fedrina; Melinda Andrika; Bedwina Antonio; Farhan Darmawan (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
This study aims to analyze the potential and development strategy of Warung Betawi Haji Apen as a local culture-based culinary tourism destination in Ragunan, South Jakarta. The research method used is descriptive qualitative through direct observation, in-depth interviews, documentation, and focus group discussions (FGDs). This study examines the 4A aspects (Attraction, Accessibility, Amenities, Ancillary) and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to evaluate the strategic position of the warung within the culinary tourism ecosystem. The results show that Warung Betawi Haji Apen offers authentic culinary appeal and a strategic location, but still faces challenges in digital promotion and limited additional facilities. The study recommends several development strategies including digital media optimization, provision of cultural interpretation materials, collaboration with travel agents, service enhancement, and staff training. By strengthening strategies based on internal strengths and external opportunities, Warung Betawi Haji Apen has great potential to become a leading culinary tourism destination while contributing to the preservation of Betawi culture